2019
DOI: 10.4102/sajhivmed.v20i1.849
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections, the silent partner in HIV-infected women in Zimbabwe

Abstract: Background: Coinfection rates of HIV and sexually transmitted infections (STIs) are not widely reported in Zimbabwe and no local guidelines regarding the screening of STIs in people living with HIV exist.Objectives: This cross-sectional study was conducted to determine the prevalence and associated risk factors for STI coinfection in a cohort of HIV-infected women.Methods: Between January and June 2016, 385 HIV-infected women presenting for routine cervical cancer screening were tested for five STIs: Neisseria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In-depth interviews with some of our participants revealed that low condom use was due to their lack of confidence about suggesting condom use to their partners, their low HIV risk perception due to poor comprehensive HIV knowledge, and intimate partner violence [30]. Low condom use among married couples and HIV-positive women has been reported in previous studies in Zimbabwe [71][72][73]. The lack of significant urban-rural disparity on condom use was not expected, and we think that it might be due in part to social desirability bias.…”
Section: Discussionmentioning
confidence: 58%
“…In-depth interviews with some of our participants revealed that low condom use was due to their lack of confidence about suggesting condom use to their partners, their low HIV risk perception due to poor comprehensive HIV knowledge, and intimate partner violence [30]. Low condom use among married couples and HIV-positive women has been reported in previous studies in Zimbabwe [71][72][73]. The lack of significant urban-rural disparity on condom use was not expected, and we think that it might be due in part to social desirability bias.…”
Section: Discussionmentioning
confidence: 58%
“…In the present study, a rather high STI prevalence among HIVpositive individuals was con rmed, namely, 47.0% (191/406) in total,45.1% (91/204) in ART-naive individuals and 49.0% (99/202) in ART individuals. This prevalence is much higher than the 5.3% observed in the HIVpositive individuals in Nepal [19], the 11.1% detected in the women living with HIV/AIDS (WLHA) in Uganda [20] and the 23.5% of HIV-infected MSM in China [21], but the prevalence was less than the 60.6% of female sex workers in Peru [22] and the 60.5% of HIV-infected Women in Zimbabwe [23]. The prevalence of genital tract discomfort was 0.5%…”
Section: Discussionmentioning
confidence: 68%
“…34 Thus, it is possible that women with HIV are more likely to be misclassified for increased cervical cancer risk as they might be less likely to clear infections because of their immune status. 35,36 These findings could also indicate that women with HIV have earlier disease progression, meaning that these women should be engaged in screening at a younger age. Efforts to change screening methods to HPV screening are underway and could help to prevent misclassification of disease in women with HIV.…”
Section: Discussionmentioning
confidence: 97%